A finite element study of interphase properties and reinforcement size effect on the electro-elastic properties of PMN-0.3PT/PDMS nanocomposite. (March 2023) - Mishra, Neelam; Das, Kaushik
Abstract: A three dimensional finite element model based on periodic boundary conditions is developed to evaluate the overall electroelastic properties of 0–3 piezoelectric polymer nanocomposites with spherical type reinforcements. The model is then used to investigate the effect of interphase (properties as well as thickness) and reinforcement size on the effective elastic, piezoelectric and dielectric properties of the nanocomposite. The results are compared with those obtained from Eshelby-Mori–Tanaka model as well as Odegard's effective interphase model. As an example of polymer nanocomposite, all the computational analysis is done for Polydimethylsiloxane (PDMS) polymer embedded with P b ( M g 1 / 3 N b 2 / 3 ) O 3 − 0 . 3 P b T i O 3 (PMN-0.3PT). It was determined that interphase properties as well as reinforcement size have strong effect on the overall properties of piezoelectric polymer nanocomposite, especially on the effective elastic properties. Graphical abstract: